Literacy in Traditional Societies - Goody, Jack (Cambridge Cambridge University Press, 1975)
The importance of writing as a means of communication in a society formerly without it, or where writing has been confined to particular groups, is enormous. It objectifies speech, provides language with a material correlative, and in this material form speech can be transmitted over space and preserved over time. In this book the contributors discuss cultures at different levels of sophistication and literacy and examine the importance of writing on the development of these societies. All the articles except the first were specially written for this book and the extensive introduction unites and synthesizes the material.
Keywords: Linguistics